2015
DOI: 10.1007/978-3-319-20328-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Layer Measurements in a Network with Bifurcating Microchannels Using a Global Approach

Abstract: One of the most interesting hemodynamic phenomenon observed in microchannels is the existence of a marginal cell-free layer (CFL) at regions adjacent to the wall. This is a well known phenomenon that occurs in simple glass capillaries and in vivo microvessels, but has never been investigated in detail in biomedical microdevices containing complex geometries. In the present chapter, in vitro blood flowing through bifurcating microchannels was studied, with the aim of characterizing the cell-free layer (CFL). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A genetic algorithm was used to solve the constrained optimisation problem and the best fit was obtained by using the function (g 3 ), i.e., a sum of trigonometric functions. This finding corroborates the results obtained by Taboada et al (2013) and Bento et al (2015) and where they have performed similar studies in microchannels networks and have found that the function (g 3 ) is the one that best fit to their CFL measurements. As a future work, we will test other functions and examine a bigger variety of physiological fluids used in vitro blood studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A genetic algorithm was used to solve the constrained optimisation problem and the best fit was obtained by using the function (g 3 ), i.e., a sum of trigonometric functions. This finding corroborates the results obtained by Taboada et al (2013) and Bento et al (2015) and where they have performed similar studies in microchannels networks and have found that the function (g 3 ) is the one that best fit to their CFL measurements. As a future work, we will test other functions and examine a bigger variety of physiological fluids used in vitro blood studies.…”
Section: Discussionsupporting
confidence: 92%
“…Individuals with less value have a high probability of being selected whereas the new generation of individuals may have a minor objective value than the previous generation. The evolution process is repeated until the stopping criterion is satisfied (Bento et al, 2013(Bento et al, , 2015Catlin et al, 2011;Kumar et al, 2010). In this work it was implemented the genetic algorithm proposed by Bento et al (2013Bento et al ( , 2015 using Matlab software.…”
Section: Global Optimisation Method: Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation